THE EMERGENCE OF SECONDARY URBAN CENTERS OR THE WITHDRAWAL OF URBAN CENTRALITY TO THE SUBURBS: A CASE STUDY OF THE CITY OF TÉBESSA IN THE FAR EAST OF ALGERIA - Abderraziq Djakjak; Brahim Djebnoune; Berrehail Guendouz (International Journal of Innovative Technologies in Social Science, 2024)
Major Algerian cities have witnessed significant dynamics, causing radical functional transformations that impacted city centers and their suburbs, leading to changes in the traditional image of cities. This resulted in a new distribution of urban functions and a redefinition of the concept of "space." Consequently, the current expansion and extension of cities’ urban structure has encouraged a new relationship between the center and suburb, where new points of attraction have emerged on the "margins and suburbs," resulting in "**new centralities**" that caused major transformations affecting urban communities, spaces, and functions. The city of Tébessa, like other cities and being a border city and transit area to the Tunisian border, has experienced a new form of urban spaces. It previously had a traditional urban centrality around the Byzantine wall, one of the city’s landmarks, which dominated for a long time as a central point over the rest of the urban space (the center). However, in recent years, it has undergone major transformations, characterized by strong attraction of functions, activities, and services, especially commercial activity in some city neighborhoods such as Skanska district, Constantine Road district, and Annaba Road district, in addition to “La Rocade” district, which plays a fundamental role in drawing a new image of centralities within Tébessa city at present. Therefore, this modest research was primarily based on fieldwork through a survey of residents in the four mentioned neighborhoods and the use of field observation through an observation network of service and commercial activities within the urban space concerned by the study. Thus, attempting to show whether there are signs of emergence of new urban centrality models that have gradually begun to take their place in Tébessa city, which is characterized by functional and economic diversity (in the city suburbs).